Evolution of Purogangri Ice Cap, central Tibetan Plateau, 2000-2012 - a comparison of two glaciological methods - Huintjes, E.; Neckel, N.; Maussion, F.; Spieß, M.; Scherer, D.; Hochschild, V.; Sauter, T.; Schneider, C. (Universität Tübingen, 2013)
Abstract HKT-ISTP 2013 BP